Alice Munro as the master of story telling: The Love of a Good Woman: Exploring Alice Munro's Masterful Use of Complicated Narratives in 'The Love of a Good Woman' (Journal of Advances and Scholarly Researches in Allied Education, 2021)
here are many people who have commented on Alice Munro's ability to create complicatednarratives. Digression or deferral, discontinuity, layering, and so on are only a few examples of how TheLove of a Good Woman defies short narrative form. Traditional theories of reading do not adequatelyexplain how good apprenticeship with Munro's short stories may be achieved, according to Ross(2002). When it comes to teaching complicated narratives to students, this study examines Munro'screative skill in The Love of A Good Woman and offers forth a method for easing students'comprehension of difficult narratives. Writing in an online wiki encourages pupils to engage in theprocess of layering story and building and questioning complicated narrative linkages, it is said. Inturn, this creative activity may aid their comprehension of short stories like Munro's.